Faktor-Faktor yang Mempengaruhi Kemauan Membayar Pajak WPOP di Kantor Pelayanan Pajak Pratama Gianyar - Pringgandana, Aswin; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi, 2019)
The purpose this study is to determine the effect of awareness tax, knowledge and understanding of tax regulations, the effectiveness of tax system, the quality of tax services on the willingness to pay personal taxpayers. This research was conducted at KPP Pratama Gianyar. The population is individual taxpayer registered in KPP Pratama Gianyar as many 114,677 taxpayer with the amount of samples taken as 100 personal tax payers with incidental sampling technique by filling out the questionnaire. Analysis technique used multiple linear regression. Based on the results found that awareness tax, knowledge and understanding, tax system effectiveness, and quality of tax services have a positive and significant impact on the willingness to pay taxes. This shows that the higher level of awareness of paying taxes, knowledge and understanding of tax laws, the effectiveness of the tax system, the quality of tax services will be higher the willingness to pay taxes. Keywords: awareness, knowledge, understanding, effectiveness, service quality